Bioreactors, scaffolds and microcarriers and in vitro meat production—current obstacles and potential solutions - Kulus, Magdalena; Jankowski, Maurycy; Kranc, Wiesława; Golkar Narenji, Afsaneh; Farzaneh, Maryam; Dzięgiel, Piotr; Zabel, Maciej; Antosik, Paweł; Bukowska, Dorota; Mozdziak, Paul; Kempisty, Bartosz (Frontiers in Nutrition, 2023)
In vitro meat production presents a potential viable alternative for meat consumption, which could provide the consumer with a product indistinguishable from the original, with very similar nutritional and culinary values. Indeed, the alternative products currently accessible often lack comparable nutritional value or culinary attributes to their animal-derived counterparts. This creates challenges for their global acceptance, particularly in countries where meat consumption holds cultural significance. However, while cultured meat research has been progressing rapidly in recent years, some significant obstacles still need to be overcome before its possible commercialization. Hence, this review summarizes the most current knowledge regarding the history of cultured meat, the currently used cell sources and methods used for the purpose of in vitro meat production, with particular focus on the role of bioreactors, scaffolds and microcarriers in overcoming the current obstacles. The authors put the potential microcarrier and scaffold-based solutions in a context, discussing the ways in which they can impact the way forward for the technology, including the use of considering the potential practical and societal barriers to implementing it as a viable food source worldwide.